2019
DOI: 10.2340/16501977-2550
|View full text |Cite
|
Sign up to set email alerts
|

Switching from onabotulinumtoxin-A to abobotulinumtoxin-A in children with cerebral palsy treated for spasticity: A retrospective safety and efficacy evaluation

Abstract: In the absence of head-to-head clinical trials, a retrospective observational study of 118 children with cerebral palsy who had switched botulinum toxin formulation (from onabotulinumtoxin-A to abobotulinumtoxin-A) due to a change in hospital policy was performed. The safety and tolerability profile of both formulations were similar. Likewise, the efficacy of treatment (measured 4-6 weeks post-injection) was found to be similar for all clinical measures assessed. This study indicates that switching from onabot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The main conclusions above are consistent with findings from other economic studies in PLL. In real-world longitudinal studies, abobotulinumtoxinA has been reported to be similarly or more effective and less costly than onabotulinumtoxinA 35,[38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…The main conclusions above are consistent with findings from other economic studies in PLL. In real-world longitudinal studies, abobotulinumtoxinA has been reported to be similarly or more effective and less costly than onabotulinumtoxinA 35,[38][39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences between the preparations in terms of efficacy and safety, but none of the studies compared them directly. Two other papers have described the transition from OnaBoNT-A to AboBoNT-A for economic or administrative reasons [36,37]. The authors found no differences in the efficacy or safety of the treatment.…”
Section: E a D I N G T O P I Cmentioning
confidence: 94%
“…Such information on the potential differences of each product is of great importance to inform treatment decisions. For example, a switch from one BoNT-A to the other might be necessary as per physician’s decision based on patient medical needs to optimize treatment outcomes or based on hospital/insurance budgetary directives for financial considerations [ 15 , 16 ]. Moreover, recent data from a patient survey in spasticity indicate that > 80% patients with spasticity are living with significant symptom re-emergence between injections [ 17 ], and an understanding of the duration of benefit will be important in ensuring this ‘rollercoaster’ of symptoms is reduced or avoided.…”
Section: Introductionmentioning
confidence: 99%